MicroRNAs in dilated cardiomyopathy: from biomarkers to therapeutic targets - Abisha Vince Jeo V S; P. S. Sneha Sandra; Mahesh Mundalil Vasu; Jeemon Panniyammakal; Sanjay Ganapathi; Madhusoodanan Urulangodi; Neethu Mohan; P. R. Anil Kumar; Srikant Ambatipudi; Jyothi Vijay; Sivadasanpillai Harikrishnan (Molecular Biology Reports, 2026)

Diverse weed control approaches for sustainable vegetable peas production: Insights into herbicide residues and soil biology - Ramanjit Kaur; Chinnali Das; Suman Sen; Manpreet Jaidka; Sunil Kumar; Teekam Singh; R. S. Bana; S. L. Meena; T. K. Das; Anchal Dass; Seema Sepat; Neethu Narayanan (Phytoparasitica, 2026)

Performance Evaluation of EOS-06 OCM-3 Chlorophyll-a Retrievals in Case-1 Waters - Chiranjivi Jayaram; Neethu Chacko; Rajdeep Roy; T. Devi Varaprasada Rao; P. V. Nagamani; T. V. S. Udaya Bhaskar; K. N. Babu; Prakash Chauhan (Journal of the Indian Society of Remote Sensing, 2026)

Intelligent quantification of ecotoxic fungicide in viticultural environment using AI-driven non-isotropic GPR integrated electrochemical sensor - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Qianqiao Chen; Salman S. Alharthi; Hamed M. Al-Saidi (Journal of Environmental Chemical Engineering, 2026)

Electrochemical quantification of O-phenylphenol in citrus fruits and oilseeds using β-CD-carbon black/CuCo2O4 nanocomposite - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Aiswarya H N; Salman S. Alharthi; Hamed M. Al-Saidi (Food Control, 2026)

Cadmium toxicity in the black clam Villorita cyprinoides (Gray 1825): insights for developing seawater quality criteria - K V Neethu; N Deepak Sankar; P Hari Praved; S R Marigoudar; K V Sharma (Journal of Earth System Science, 2026)

Effect of Blanching Conditions on the Quality of Infrared-Dried Squid Rings: Sensory-Based Optimization and Semi-Empirical Drying Modeling - K. C. Neethu; Lakshmi Dayal; D. S. Aniesrani Delfiya; Remya S; Murali S; George Ninan (Journal of Aquatic Food Product Technology, 2026)

Tracing genotoxic malachite green contamination in aquatic environment using α-Co₂V₂O₇/PAH-CNTs-based electrochemical sensor - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; H.N. Aiswarya; Salman S. Alharthi; Hamed M. Al-Saidi (Journal of Environmental Chemical Engineering, 2025)

Quantification of systemic fungicide in stone fruits and nuts based on PVP/CNF-COOH embedded CuCo2O4 tertiary nanocomposite - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Salman S. Alharthi; Hamed M. Al-Saidi (Food Chemistry, 2025)

Unraveling the invisible threat of microplastics to Lakshadweep Coral Atolls, Indian Ocean: Multifaceted ecological risk and pollution profiling - P. Hari Praved; P. Sreeraj; K.V. Neethu; S. Bijoy Nandan; Suraj Ravindran; S.R. Marigoudar (Journal of Hazardous Materials, 2025)

Genome analysis, identification, and expression analysis of nitrogen and potassium responsive genes in cassava - Swathy Sivan; Senthilkumar K. Muthusamy; M. N. Sheela; K. Arya; B. S. Revathi; P. V. Abhilash; R. S. Neethu; A. Pooja; B. S. Prakash Krishnan (Acta Physiologiae Plantarum, 2025)

Multidimensional risk assessment of marine litter pollution in the ecologically fragile coral atolls of India - P. Hari Praved; K.V. Neethu; S. Bijoy Nandan; N.G. Athul Krishna; B.P. Aneesh; N. Deepak Sankar; Hanse Antony; E.H. Aravind (Journal of Environmental Management, 2025)

Ultrasensitive quantification of neonicotinoid thiamethoxam in environment using MOF-derived CuCo2O4/3D rGO based electrochemical sensor integrated with optimized neural network - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Salman S. Alharthi; Hamed M. Al-Saidi (Environmental Research, 2025)

Cuprospinel decorated biopolymer functionalized CNFs based electrocatalytic platform integrated with grid search optimized neural network for detection of vital amino acid in beverages - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Salman S. Alharthi; Hamed M. Al-Saidi (Food Chemistry, 2025)

Captive breeding, embryonic development, and conservation of the endangered catfish, Horabagrus nigricollaris (Pethiyagoda & Kottelat 1994): a first report - C.P Abhilash; Charan Ravi; Saikrishnan K.R; Sarath Varghese; Neethu Z; Chandana B.L; Ajith Kumar T.T; Uttam Kumar Sarkar; V. S. Basheer (Aquaculture International, 2025)

Corrigendum to “Synthesis and characterization of β-carotene nano-formulation and its application in physiochemical properties of ice cream” [Food and Humanity 1 (2023) 1379–1387] - Neethu Hari; B. Lekshmi Vinod; Vinie Solomon; Athira S. Dev; A. Gangaprasad; Ananthakrishnan Jayakumaran Nair (Food and Humanity, 2024)

Evaluation of Fulgoraecia melanoleuca (Fletcher) (Lepidoptera: Epipyropidae) Releases for the Management of Pyrilla perpusilla (Walker) (Hemiptera: Lophopidae) on Sugarcane in Punjab, India - Neethu Maria Augustine; P. S. Shera; Rajinder Kumar; Sudhendu Sharma (Sugar Tech, 2024)

Resonating eco-legacies: unravelling colonial tapestries in Amitav Ghosh’s The Great Derangement and The Nutmeg’s Curse - M. S. Neethu; R. Bhuvaneswari (Regional Environmental Change, 2024)

Response Surface Optimization of Steam Blanching Conditions of Shrimp ( Metapenaeus dobsoni ) for Drying in Solar-Electrical Hybrid Dryer - K. C. Neethu; Anuja R. Nair; S. Remya; S. Murali; D. S. Aniesrani Delfiya; George Ninan (Journal of Aquatic Food Product Technology, 2024)

Nanomolar electrochemical detection of feed additive ractopamine in meat samples using spinel zinc ferrite decorated 3-dimensional graphene nanosheets to combat food fraud in livestock industries - Deepak Balram; Kuang-Yow Lian; Neethu Sebastian; Salman S. Alharthi; Hamed M. Al-Saidi; Deepak Kumar (Food Chemistry, 2024)

Evaluation of microplastic pollution and risk assessment in a tropical monsoonal estuary, with special emphasis on contamination in jellyfish - P. Hari Praved; K.V. Neethu; S. Bijoy Nandan; N. Deepak Sankar; E.H. Aravind; Sruthy Sebastian; S.R. Marigoudar; K.V. Sharma (Environmental Pollution, 2024)

Ultrasensitive detection and photocatalytic degradation of polyketide drug tetracycline in environment and food samples using dual-functional Ag doped zinc ferrite embedded functionalized carbon nanofibers - Neethu Sebastian; Wan-Chin Yu; Deepak Balram; Guo-Ting Hong; Salman S. Alharthi; Hamed M. Al-Saidi (Chemosphere, 2024)

Synthesis and characterization of β-carotene nano-formulation and its application in physiochemical properties of ice cream - Neethu Hari; Lekshmi Vinod B; Vinie Solomon; Athira S. Dev; A. Gangaprasad; Ananthakrishnan Jayakumaran Nair (Food and Humanity, 2023)

Patterns and variability in the microplastic contamination along the southwest coast of India with emphasis on submarine groundwater discharge sites - Aishwarya Purushothaman; N.K. Vishnudattan; S.P. Nehala; M.D. Meghamol; K.V. Neethu; Jorphin Joseph; S. Bijoy Nandan; K.B. Padmakumar; Lathika Cicily Thomas (Marine Pollution Bulletin, 2023)

Unusual blooming of invasive ctenophore Beroe ovata (Bruguière, 1789) and geographical range expansion based on morphology and molecular analysis - P. Hari Praved; Otto M.P. Oliveira; K.V. Neethu; Nazar M. Suhaana; S. Bijoy Nandan; P.R. Jayachandran (Regional Studies in Marine Science, 2023)

In Silico and In Vitro Analyses Reveal Promising Antimicrobial Peptides from Myxobacteria - Benita S. Arakal; David E. Whitworth; Philip E. James; Richard Rowlands; Neethu P. T. Madhusoodanan; Malvika R. Baijoo; Paul G. Livingstone (Probiotics and Antimicrobial Proteins, 2023)
Antimicrobial resistance (AMR) is a global concern, and as soon as new antibiotics are introduced, resistance to those agents emerges. Therefore, there is an increased appetite for alternative antimicrobial agents to traditional antibiotics. Here, we used in silico methods to investigate potential antimicrobial peptides (AMPs) from predatory myxobacteria. Six hundred seventy-two potential AMP sequences were extracted from eight complete myxobacterial genomes. Most putative AMPs were predicted to be active against Klebsiella pneumoniae with least activity being predicted against Staphylococcus aureus . One hundred seventeen AMPs (defined here as ‘potent putative AMPs’) were predicted to have very good activity against more than two bacterial pathogens, and these were characterized further in silico. All potent putative AMPs were predicted to have anti-inflammatory and antifungal properties, but none was predicted to be active against viruses. Twenty six (22%) of them were predicted to be hemolytic to human erythrocytes, five were predicted to have anticancer properties, and 56 (47%) were predicted to be biofilm active. In vitro assays using four synthesized AMPs showed high MIC values (e.g. So_ce_56_913 250 µg/ml and Coral_AMP411 125 µg/ml against E. coli ). However, antibiofilm assays showed a substantial reduction in numbers (e.g. Coral_AMP411 and Myxo_mac104 showed a 69% and 73% reduction, respectively, at the lowest concentration against E. coli ) compared to traditional antibiotics. Fourteen putative AMPs had high sequence similarity to proteins which were functionally associated with proteins of known function. The myxobacterial genomes also possessed a variety of biosynthetic gene clusters (BGCs) that can encode antimicrobial secondary metabolites, but their numbers did not correlate with those of the AMPs. We suggest that AMPs from myxobacteria are a promising source of novel antimicrobial agents with a plethora of biological properties.

Eliciting heavy metal contamination on selected native organisms from Cochin estuary using contemporary biomarker approach - N D Don Xavier; S Bijoy Nandan; P R Jayachandran; K V Neethu; D Mohan; S R Marigoudar (Journal of Earth System Science, 2021)

Anomalous Reduction of the Total Suspended Matter During the COVID-19 Lockdown in the Hooghly Estuarine System - Chiranjivi Jayaram; Rajdeep Roy; Neethu Chacko; Debadatta Swain; Ramunaidu Punnana; S. Bandyopadhyay; S. B. Choudhury; Dibyendu Dutta (Frontiers in Marine Science, 2021)
The impact of the coronavirus disease 2019 (COVID-19) lockdown in the Hooghly estuarine region, India is assessed using the total suspended matter (TSM) concentration. The estimation of TSM is performed using Landsat-8/operational land imager (OLI), and an intercomparison of TSM load during the pre-lockdown and lockdown periods is done. It is observed that during the lockdown period, TSM reduced by 30–50%. This is a significant observation considering the ecological balance of the region and the fact that it is home to the largest mangroves in the world. This change in suspended matter presumably reflects the influence of reduction in anthropogenic activities owing to the COVID-19 lockdowns, such as industries, closure of shipping activities (through less dredging), and brick kilns (through less sediment removal), which are generally the primary contributors in this region. Even though these observed changes are representative of the positive influence of the COVID-19 lockdown, its implications in estuarine biogeochemistry still remain poorly quantified. The decrease in TSM content may increase light penetration, thereby increasing the primary productivity. In addition, low sediment load reaching the Bay of Bengal could influence the carbon export due to reduction in ballasting effect as reported from this region. In summary, the influence of the COVID-19 lockdown on the biogeochemistry of the aquatic ecosystem appears rather complex than thought earlier and may vary regionally based on local hydrodynamics. The analysis elucidates the complex interplay of regional lockdown and its implication in modulation of local biogeochemistry. However, the relative importance of each process in the Hooghly estuary remains to be fully evaluated.

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Habitat Suitability Analysis of Himalayan Musk Deer (Moschus leucogaster) in Part of Western Himalaya, India - Subrata Nandy; M. Neethu Lakshmi; S. P. S. Kushwaha (Journal of the Indian Society of Remote Sensing, 2020)

Egg and Larval Development of Serranid Fish Marcia’s Anthias, Pseudanthias marcia (Subfamily: Anthiinae) Spawned and Reared under Captive Condition - Gomathi P; Anil M K; Raheem P K; P. Neethu Raj; M. V. Rohini Krishna; Ambarish P. Gop; Surya S (Thalassas: An International Journal of Marine Sciences, 2020)

Epigenetic Modifier Based Enhancement of Piperine Production in Endophytic Diaporthe sp. PF20 - B. Jasim; Neethu Sahadevan; S. Chithra; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Evaluation of SARAL / AltiKa Measured Significant Wave Height and Wind Speed in the Indian Ocean Region - Chiranjivi Jayaram; Saurabh Bansal; A. Sai Krishnaveni; Neethu Chacko; V. M. Chowdary; D. Dutta; K. H. Rao; C. B. S. Dutt; J. R. Sharma; V. K. Dadhwal (Journal of the Indian Society of Remote Sensing, 2016)